KEADILAN GENDER DALAM PEMBAGIAN WARIS: ANALISIS TEMATIK QS. AN-NISA AYAT 7, 11, 12 DAN 176 - Indah Saputri; Askahar; Muhammad Ramadhan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the interpretations of classical and modern exegeses concerning the verses on inheritance in QS An-Nisā’ verses 7, 11, 12, and 176, as well as to examine their relevance to the principle of women's justice. Ibn Kathir's exegesis is selected as a representation of classical interpretation that adheres to the bi al-ma’tsur approach, while M. Quraish Shihab is chosen as a representation of modern interpretation that employs contextual and hermeneutic approaches. This research employs a qualitative method with a literature study approach through text analysis of exegeses, scientific journals and other supporting literature. The findings indicate that classical exegesis understands the distribution of inheritance as a final decree based on the social structure at the time the verses were revealed, whereas modern exegesis emphasizes substantive justice that considers the changing social roles of women in the contemporary era. This study concludes that the principle of women's justice in the verses on inheritance is flexible through the maqāṣid al-syarī‘ah approach, thus remaining relevant in the context of modern social developments. Consequently, this research provides significant contributions in bridging the understanding between classical and modern exegesis traditions, as well as reinforcing the position of women as rightful, dignified, and legally protected heirs under Islamic law.